Biomechanical analysis of hip, knee, and ankle joint contact forces during squats in elite powerlifters - Alexander Pürzel; Paul Kaufmann; Willi Koller; Elias Kaj Wallnöfer; Arnold Baca; Hans Kainz (PLoS ONE, 2025)
The squat is one of three lifts within the sport of powerlifting. This study examined how increasing intensity in the squat affects joint contact forces in elite powerlifters. Twenty-nine Austrian top-ranked powerlifters (16 male, 13 female) performed squats at 70% to 90% of their one-repetition maximum (1-RM). 3D motion capture and force plate data were used to estimate joint contact forces using musculoskeletal modelling. In contrast to the hip and ankle joints, which exhibited peak resultant joint contact forces in the deepest squat positions, the tibiofemoral and patellofemoral joints maintained consistently high loads over a broad portion of the squat cycle. During large parts of the concentric phase, the resultant joint contact forces did not significantly differ between intensity conditions, with the exception of the hip joint contact force. At 90% 1-RM, average peak joint contact forces reached 15.5 ± 3.0 times body weight (BW), 23.2 ± 3.9 BW, 26.7 ± 4.3 BW, and 11.5 ± 2.2 BW for the hip, tibiofemoral, patellofemoral, and ankle joint, respectively. The high and sustained joint contact forces observed in our study emphasise the need for load management strategies to optimise performance and reduce injury risk. These insights offer a valuable foundation for tailoring strength training programs and supporting long-term joint health in high-performance athletes.